2018
DOI: 10.1016/j.sedgeo.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Trace fossils, sedimentary facies and parasequence architecture from the Lower Cretaceous Mulichinco Formation of Argentina: The role of fair-weather waves in shoreface deposits

Abstract: In presenting this thesis in partial fulfillment of the requirements for a Postgraduate degree from the University of Saskatchewan, I agree that the Libraries of this University may make it freely available for inspection. I further agree that permission for copying this thesis in any manner, in whole or in part, for scholarly purposes may be granted by the professor or professors who supervised my thesis work or, in their absence, by the Head of the Department or the Dean of the college in which my thesis wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…Meters-thick amalgamated HCS and SCS deposits, and a generally much-better sorted succession than the one documented in this study, were reported from the same study. Wesolowski et al (2018) further identified upper shoreface deposits, which arguably positions the locality marginally closer to the shoreline than the deposits documented in this study. Nevertheless, Wesolowski et al (2018) concluded that Puerta Curaco was entirely wavedominated (non-tidal) and did not identify any sign of tidal influence (Figure 12).…”
Section: Sediment Dispersal and Process Mixingsupporting
confidence: 63%
See 2 more Smart Citations
“…Meters-thick amalgamated HCS and SCS deposits, and a generally much-better sorted succession than the one documented in this study, were reported from the same study. Wesolowski et al (2018) further identified upper shoreface deposits, which arguably positions the locality marginally closer to the shoreline than the deposits documented in this study. Nevertheless, Wesolowski et al (2018) concluded that Puerta Curaco was entirely wavedominated (non-tidal) and did not identify any sign of tidal influence (Figure 12).…”
Section: Sediment Dispersal and Process Mixingsupporting
confidence: 63%
“…See legend for facies and trace fossils; letters refer to Dashtgard et al (2012) to include tidal flat environment; plots include upper Mulichinco Fm. bulk locality plots for this study's four study localities, approximate bulk plot for the study area in blue-green, and bulk plot for the Puerta Curaco area in gray (Wesolowski et al, 2018) The dataset exhibits a gently increased storm wave dominance toward southwest (Figure 10). Cerro Pampa Tril records the thickest accumulation of mixed wave-and tide-influenced deposits (between FS5.2 and FS6, Figure 10) and accommodates the highest concentration of storm deposits of this study (between FS6.1 and FS6.2; Figure 10).…”
Section: Sediment Dispersal and Process Mixingmentioning
confidence: 97%
See 1 more Smart Citation
“…; Wesolowski et al . ). Recent occurrences of similar traces were reported in deep‐marine environments of the Bay of Bengal (Ohta ; Gaillard ; Stanley & Pickerill ) and the tidal flat of Inchon, Korea (Frey et al .…”
Section: Radial To Rosette Ichnofossilsmentioning
confidence: 97%
“…Phycosiphon is common in ox y gen-and nu tri ent-rich fine-grained siliciclastic softground de pos its (Rodríguez-Tovar et al, 2014a). This ichnospecies is char ac ter is tic of the prox i mal and dis tal lower shoreface to lower off shore and even deep-sea set tings in calmer con di tions (Dashtgard et al, 2012;Vakarelov et al 2012;Wesolowski et al, 2018;MacEachern and Bann, 2020). It is known from the Cam brian to the Ho lo cene (Naruse and Nifuku, 2008;Hammersburg et al, 2018).…”
Section: Ophiomorpha Lundgren 1891mentioning
confidence: 99%